A coral-like Mo2C/TiO2 photoelectrode for photoelectrochemical water splitting - Siti Nurul Falaein Moridon; Khuzaimah Arifin; Lorna Jeffery Minggu; Mohamad Azuwa Mohamed; Masliana Muslimin; Ahmad Zaki Zaini; Mohammad Kassim (Penerbit Universiti Kebangsaan Malaysia, 2023)
Titanium dioxide (TiO2) is one of the most explored photoelectrode materials of water splitting for hydrogen generation. However, TiO2 has a bandgap of 3.2 eV, which restricts its energy absorption to UV light, and the photoexcited electrons and holes swiftly recombine. Thus, alteration of the band structure, such as by adding materials as cocatalysts, is needed. 2D molybdenum carbide (Mo2C) has been researched extensively as an excellent non-noble cocatalyst owing to its Pt-like H+ adsorption capacity and high conductivity. In this work, composites of TiO2 and Mo 2C with four different compositions were produced using the sol-gel method, and their photoelectrochemical activity for water splitting was assessed. The composites were spin-coated onto FTO conducting glass, and FESEM analysis indicated that TiO2nanoparticles are widely disseminated across Mo2C to form coral-like structures. Analysis via X-ray diffraction verified the existence of peaks composed of TiO2 and Mo2C. The sample containing 3% Mo2C had the greatest increase in photocurrent density, which was approximately 1.56 mA cm-2 at a potential of 1.0 V against Ag/AgCl (1.59 vs. RHE), which is five times that of bare TiO2. In addition, the composite’s onset potential moved to a lower potential. Our findings suggest that adding Mo2C increases the photoelectrochemical performance of the TiO2 photoelectrode. This work indicates the feasibility of employing Mo2C as a cocatalyst to improve the performance of TiO 2 for photoelectrochemical H2 production.